Menelisik Konflik Peran Guna Work-Life Balance Pekerja Wanita - Ni Putu Ayu Indira Yuni; Gede Sri Darma (Universitas Pendidikan Nasional, 2022)
Married female workers in Bali face various challenges related to work, culture, and household responsibilities, often resulting in conflicts in their roles. These role conflicts affect both their work productivity and quality of life. This study aims to explore the different types of role conflicts that occur and the efforts made to avoid such conflicts and achieve work-life balance. Using qualitative methods and a phenomenological analysis approach, data was collected through semi-structured interviews with 10 female workers in the formal sector in Bali. The study found that two categories of role conflicts occur: work interference with personal life and personal life interference with work. The efforts made to resolve these conflicts include maintaining good communication, involving family members to help with tasks, and managing work schedules. In achieving work-life balance, the study found that family support and other factors positively influence work performance. Female workers can also contribute to their family's financial needs and have a desire to apply their knowledge to their work. Overall, this study highlights the importance of addressing role conflicts among married female workers in Bali to enhance their work productivity and quality of life.